The commodification of economic perspectives in Islamic Religious Education Studies on social media - Heri Fathurahman; Umasih Umasih; Gumgum Gumelar; Andy Hadiyanto; Assyifa Amelia Azzahra (Informasi, 2021)
Economic empowerment in Indonesia is quite dynamically developing, this is also not free from the study of Islamic religious education on Islamic economics. Apart from this, researchers also used YouTube social media for review in this study. The formulation of the research problem is how to commodify an economic perspective in the study of Islamic religious education on social media. This study aims to analyze the commodification of economic perspectives in the study of Islamic religious education on social media. Researchers use a quantitative approach with a survey method where data will be taken from a predetermined population and sample and then a questionnaire to the respondent. The results of this study indicate that the commodification of YouTube content about the economy packaged in Islamic Religious Education affects the attitudes of YouTube users who watch the content. This is evidenced by conducting a regression test with the results that all ha received and accepted are declared good. In addition, economic empowerment in the perspective of Islamic religious education can also increase community economic empowerment and support the economic activities of the Indonesian people.